The Effect of Left Uterine Displacement and Intravenous Ephedrine for Prevention of Hypotension Following Spinal Anesthesia in Cesarean Section in Maharat Nakhon Ratchasima Hospital. - Tanjindaprateep, Rongnapa; Susanee , Patnaree (Maharat Nakhon Ratchasima Hospital Journal, 2025)
Introduction: Hypotension following spinal anesthesia for cesarean section remains the common complication which could be prevented with intravenous preloading fluid, intravenous ephedrine and the of left utenine displacement. Objective: To investigate whether immediate intravenous ephedrine and left uterine displacement 15-300 for cesarean section will reduce the incidence of hypotension. Patients and methods: 80 patients, undergoing elective cesarean section under spinal anesthesia, were randomly allocated to be control (n=40) and experimental groups (n=40). In the latter, they were placed in the left uterine displacement 150 position and given intravenous ephedrine 6 mg immediately after spinal anesthesia while control group did not. Both groups were compared with regard to demographic data, mean arterial pressure, total intravenous fluid and total ephedrine requirement during operation Result: The patients in control group were more likely to have hypotension by 2.9 times (100%VS35%). Total dosage of ephedrine and intravenous saline given in control group were more than that of experimental group with statistically significant difference (P< 0.001) Conclusion: The study demonstrated that intravenous ephedrine 6 mg and left uterine displacement after spinal anesthesia for cesarean section may reduce rate of hypotension.